Importance of early and continuous use of protein restriction on the progression of adriamycin nephropathy - Barretti, Pasqual [UNESP]; Soares, Vitor [UNESP] (Taylor & Francis, 1999)
Three experimental protocols were carried out with the aim of evaluating the role of protein restriction on the progression of the established adriamycin-induced nephropathy, and whether the protective effect of the diet persists after the diet is discontinued. The effect of a low protein diet (LPD) was studied for 6 weeks in protocol 1, 16 weeks in protocol 2 and for 28 weeks in protocol 3. In protocol 3, one group (LL) received LPD and another (NN) was given a normal protein diet (NPD). A third group (LN) received LPD for 16 weeks and then NPD for 12 weeks and a fourth group (NL) was fed NPD for 16 weeks and then LPD for 12 weeks. In protocol I the tubulo- interstitial index (TILl) of rats on LPD (Md = 2, P25 = 0.0; P75 = 3.5) after six weeks, was smaller than that of the animals on NPD (Md = 6.0; P25 = 3.0; P75 = 8.0; p < 0.05). In protocol 2, the group taking LPD presented an area of interstitial fibrosis (IF) (Md= 0.5%, P25 0.2%; P75 = 1.9%) smaller than that of the NPD group (Md = 6.8%; P25 = 5.2%; P75 = 7.1%; P < 0.05). No significant difference in the area of glomerulosclerosis (GSA) was observed between the animals on LPD (Md = 0.0%; P25 = 0.0%, P75 = 0.0%) and NPD (Md = 0.37%; P25 = 02% P75 = 1.25%; p > 0.05). In protocol 3, the group LL showed GSA (Md = 1.3%; P25 0.6%, P75 = 2.5%) and IF (Md = 3.60/0; P25 = 1.6%; P75 = 5.9%) smaller that those of LN (GSA Md = 10.1%; P25 = 6.6%; P75 = 14.8%; IF; Md = 17.3%; P25 = 14.1%; P75 = 24,5%), NL (GSA: Md = 9.1%; P25 = 5,8%; P75 = 11.7%; IF; Md = 25.0%; P25 = 20.4%; P75 = 30%), and NN (GSA: Md = 6. 75%; P25 = 4.9%; P75 = 11.7%; IF: Md = 20.9%; P25 = 16.2%; P75 = 32.4%). In conclusion, in order to be effective, LPD must be introduced early and maintained for a long period of tune.
Keywords: Adriamycin nephropathy; Protein restriction; Proteinuria; Tubulointterstitial nephritis; doxorubicin; animal experiment; animal model; controlled study; creatinine blood level; diet therapy; early diagnosis; interstitial nephritis; kidney disease; nephritis; nonhuman; priority journal; protein diet; protein restriction; proteinuria; rat; Animals; Antineoplastic Agents; Diet, Protein-Restricted; Dietary Proteins; Doxorubicin; Kidney; Male; Nephritis; Rats; Rats, Wistar; Time Factors